Epidemiology of autism spectrum disorders: Global burden of disease 2019 and bibliometric analysis of risk factors - Li, Yang-An; Chen, Ze-Jian; Li, Xiao-Dan; Gu, Ming-Hui; Xia, Nan; Gong, Chen; Zhou, Zhao-Wen; Yasin, Gvzalnur; Xie, Hao-Yu; Wei, Xiu-Pan; Liu, Ya-Li; Han, Xiao-Hua; et al. (Frontiers in Pediatrics, 2022)
Background: To explore the geographical pattern and temporal trend of autism spectrum disorders (ASD) epidemiology from 1990 to 2019, and perform a bibliometric analysis of risk factors for ASD. Methods: In this study, ASD epidemiology was estimated with prevalence, incidence, and disability-adjusted life-years (DALYs) of 204 countries and territories by sex, location and sociodemographic index (SDI). Age-standardized rate (ASR) and estimated annual percentage change (EAPC) were used to quantify ASD temporal trends. Besides, the study performed a bibliometric analysis of ASD risk factors since 1990. Publications published were downloaded from the Web of Science Core Collection database, and were analyzed using CiteSpace. Results: Globally, there were estimated 28.3 million ASD prevalent cases (ASR, 369.4 per 100000 populations), 603790 incident cases (ASR, 9.3 per 100000 populations) and 4.3 million DALYs (ASR, 56.3 per 100000 populations) in 2019. Increases of autism spectrum disorders were noted in prevalent cases (39.3%), incidence (0.1%), and DALYs (38.7%) from 1990 to 2019. Age-standardized rates and EAPC showed stable trend worldwide over time. A total of 3991 articles were retrieved from Web of Science, of which 3590 were obtained for analysis after removing duplicate literatures. “Rehabilitation”, “Genetics & Heredity”, “Nanoscience & Nanotechnology”, “Biochemistry & Molecular biology”, “Psychology”, “Neurosciences”, and “Environmental Sciences” were the hotspots and frontier disciplines of ASD risk factors. Conclusions: Disease burden and risk factors of autism spectrum disorders remain global public health challenge since 1990 according to the GBD epidemiological estimates and bibliometric analysis. The findings help policy makers formulate public health policies concerning prevention targeted for risk factors, early diagnosis and life-long healthcare service of ASD. Increasing knowledge concerning the public awareness of risk factors is also warranted to address global ASD problem.